Pengaruh suplementasi berbagai level daun ketela pohon (Manihot utilissima. Pohl) terhadap produktifitas domba ekor gemuk yang diberi pakan basal jerami jagung (Zea mays) - Ndaru, Poespitasari Hazanah; Kusmartono, Kusmartono; Chuzaemi, Siti (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
This study aimed to evaluate the effect of cassava leaves supplementation strategy on fat-tailed sheep and to determine appropriate levels of protein derived from cassava leaves. Twenty eight fat-tailed sheep aging of 6-12 months old and weighing of 11-17 kg were used and arranged in a Randomized Complete Block Design (ANOVA) were subjected to the following treatments : (1) P0: maize stover ad libitum + cassava flour + urea (1% of DM intake); (2) P1: maize stover ad libitum + cassava flour + cassava leaves silage (0.5 g CP/kg BW); (3) P2: maize stover ad libitum + cassava flour + cassava leaves silage (1 g CP/kg BW); (4) P3: maize stover ad libitum + cassava flour + cassava leaves silage (1.5 g CP/kg BW); (5) P4: maize stover ad libitum + cassava flour + dried cassava leaves (0.5 g CP/kg BW); (6) P5: maize stover ad libitum + cassava flour + dried cassava leaves (1 g CP/kg BW); and (7) P6: maize stover ad libitum + cassava flour + dried cassava leaves (1.5 g CP/kg BW). Variables measured were feed consumption, nutrients digestibility, digestible nutrient intake, nitrogen retention, blood urea concentration, body weight gain and the number of eggs count. The results showed that cassava leaves supplementation as protein source had a highly significant effect (P <0.01) for digested CP intake and had a significant effect (P<0.05) for CP consumption and body weight gain. There were tendencies of increasing (1) DM intake; (2) OM intake; (3) DM, OM and CP digestibility; (4) digested DM intake, (5) digested OM intake, (6) N-retention; and Body Weight Gain. Supplementation of cassava leaves silage and dried cassava leaves at the level of 1.5 g CP / kg BW could reduce the number of worm eggs by 47.65% and 44.22%. Based on experimental results, it could be concluded that supplementation of dried cassava leaves on the level of 1.5 g CP / kg BW could increase the productivity and also could decrease worm eggs number.   Keywords: fat tail sheep, silage, cassava leaves, productivity